2013
DOI: 10.1136/bjophthalmol-2012-302351
|View full text |Cite
|
Sign up to set email alerts
|

Previous cyclodestruction is a risk factor for late-onset hypotony and suprachoroidal haemorrhage after glaucoma drainage device surgery

Abstract: While taking potential bias arising from the retrospective nature of the study into consideration, a history of previous cyclodestructive procedures before GDD surgery seems to be a major risk factor for suprachoroidal haemorrhage and for late-onset postoperative hypotony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
(9 reference statements)
0
14
0
6
Order By: Relevance
“…However, some studies have found that the therapeutic effect can be lost over time and in some cases repeated treatment is necessary 20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have found that the therapeutic effect can be lost over time and in some cases repeated treatment is necessary 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Fingerzählen wurde hierbei als 0,01, die Diskrimination von Handbewegungen als 0,001, Lichtscheinwahrnehmung als 0,000625 (1/1600) und nulla lux als 0,000313 (1/3200) gewertet. Die Medikation wurde durchgehend mittels eines Medikationsscores (modifiziertes Medikationsschema nach Rosentreter et al [8] bzw. Jacobi und Krieglstein [9] notiert (siehe ▶ Tab.…”
Section: Materials Und Methodenunclassified
“…Anders als bei frühpostoperativen Hypotonien kommt es bei dieser Form der Hypotonie nicht zu einem extensiven Abfluss von Kammerwasser durch Leckage, sondern das Ausmaß der Filtration über das Implantat liegt zu hoch für eine reduzierte Kammerwasserproduktion des Auges, was besonders bei Patienten mit Uveitis, multiplen Voroperationen oder bei Z. n. Zyklodestruktion auftreten kann [5,11]. Implantate mit Ventilmechanismus (z.…”
Section: Hypotonie ≥ 6 Wochenunclassified
“…Dies war in Beobachtungen begründet, dass ein frühzeitigerer Einsatz der Implantate zu deutlich besseren Ergebnissen führte. In diesem Kontext möchten wir auch auf den Einsatz von zyklodestruktiven Verfahren vor einer Drainageimplantat-OP hinweisen, welcher zu massiven Problemen intra-und postoperativ führen kann (frühe und späte postoperative Hypotonien, suprachoroidale Blutungen) [5].…”
Section: Introductionunclassified